2017
DOI: 10.1021/acs.energyfuels.6b02832
|View full text |Cite
|
Sign up to set email alerts
|

Partially Homogenous Charge Compression Ignition Engine Development for Low Volatility Fuels

Abstract: Control of harmful pollutants such as oxides of nitrogen (NOx), particulate matter (PM)/ soot, carbon monoxide (CO), and hydrocarbons (HC) emitted by diesel engines is essential in order to protect the environment and human health. Different versions of low temperature combustion (LTC) concepts have shown their potential in controlling these pollutants, while achieving thermal efficiencies similar to conventional compression ignition (CI) engines. In this study, a diesel fueled partially premixed homogeneous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…It is probably because EGR diluted the oxygen entering the cylinder and prolonged the ID period, thereby compressing the combustion time, which resulted in high EGT [38]. This performance is slightly different from that observed in other studies [35,39]. It was found that EGT decreased with the growth of EGR rate, mainly because EGR reduced the temperature in the cylinder.…”
Section: Engine Performancecontrasting
confidence: 62%
“…It is probably because EGR diluted the oxygen entering the cylinder and prolonged the ID period, thereby compressing the combustion time, which resulted in high EGT [38]. This performance is slightly different from that observed in other studies [35,39]. It was found that EGT decreased with the growth of EGR rate, mainly because EGR reduced the temperature in the cylinder.…”
Section: Engine Performancecontrasting
confidence: 62%
“…Wu et al [18] designed a variable cross-section dual-channel chamber and optimized the swirl rate, fuel consumption rate, and emission performance in a single-cylinder diesel engine. Singh et al [19] conducted experiments on a two-cylinder diesel engine to explore the feasibility of lowtemperature combustion, where the combustion phasing is an important parameter in the combustion process. Ni et al [20] conducted an external characteristic experiment on a two-cylinder diesel engine, and found that Brake Specific Fuel Consumption (BSFC) could be significantly reduced by about 6% by improving the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…10 In order to further reduce engine-out soot, several strategies, such as exhaust gas recirculation (EGR) and partially premixed charge compression ignition, are adopted to advanced diesel engines. 1114…”
Section: Introductionmentioning
confidence: 99%
“…10 In order to further reduce engine-out soot, several strategies, such as exhaust gas recirculation (EGR) and partially premixed charge compression ignition, are adopted to advanced diesel engines. [11][12][13][14] With one method for advanced combustion strategies, irregular shapes of the piston bowl have been developed to improve the quality of air-fuel mixing through the swirl and subsequently optimize combustion. 15 However, spray impingement tends to occur in compact-size engines with irregular shapes of the piston bowl.…”
Section: Introductionmentioning
confidence: 99%